Ampliação do repertório de crianças com Transtorno do Espectro Autista (TEA) após uma intervenção comportamental não intensiva - Manoni, Nathalia de Vasconcelos (Universidade Federal de São Carlos, 2019)
It is known the people with developmental disorders, such as Autism Spectrum Disorder (ASD), present significant deficits in the various areas of development. The ABA behavioral intervention (in English: Applied Behavior Analysis – Applied Behavior Analysis) is the one that shows the greatest evidence of effectiveness and it consists on assessing and intervening in a systematic and progressive manner, favoring repertories of the child in all areas of development, such as: language socialization, self-care, academic skills (Languages, History, Mathematics, etc), motor skills, among others. The purpose of this study was to analyze in retrospect the effects of a non-intensive intervention (1 hour and 30 minutes to 3 hours per week), applied by an interdisciplinary team to 4 children diagnosed with ASD. The following steps were analyzed: pretests to assess the children’s input repertoire; intervention applied by professionals during a maximum of twenty-two (22) months, and two post-tests carried out during and after the intervention period. The effectiveness measures of the non-intensive intervention were presented and discussed according to the skills and parameters described by Verbal Behavior Milestones Assessment and Placement Program-guide – VBMAPP (Sundberg, 2008). It was evidenced gains in repertoire of the children with ASD, specially on language skills. The research results suggest that the effectiveness of the non-intensive intervention was facilitated by the interdisciplinary approach based on ABA principles. It is expected that the discussion on the obtained results and the structure of the analyzed intervention can provide information for the planning and implementation of more accessible interventions for families of the children with ASD, when compared to the cost of intensive interventions.
Expansion of the repertoire of children with Austism Spectrum Disorder (ASD) after a non-internsive behavioral intervention
Keywords: Intervenção ABA; Intervenção não intensiva; Equipe Interdisciplinar; Ampliação de repertório; TEA; ABA intervention; Non-intensive intervention; Interdisciplinary Team; Expansion of repertoire; ASD; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM